Social skills training with a tabletop role-playing game, before and during the pandemic of 2020: in-person and online group sessions - Henning, Germano; de Oliveira, Reinaldo Rodrigo; de Andrade, Marcus Túlio Pereira; Gallo, Renato Villela; Benevides, Raissa Roberti; Gomes, Rodrigo Antonio Fuga; Fukue, Lucas Eiji Kong; Lima, Arthur Vaciloto; de Oliveira, Maria Beatriz Baggio Z. N.; de Oliveira, Daniel Amorim Medeiros; Werpp, Morgana; Moraes, Lucas; et al. (Frontiers in Psychiatry, 2024)
Background The area of social skills is broad, in theory and in practice. For social skills training, various clinical practices have been applied in group sessions, as have motivational resources such as role-playing games (RPGs). In recent years, the need arose to assess the clinical impact of the pandemic. The objective of this study was to determine the impact that the pandemic has had on in-person and online social skills training. Methods We evaluated six subjects with autism spectrum disorder, with or without another, similar disorder, each of whom attended a total of 12 two-hour RPG sessions over a 12-month period. The original (Portuguese-language) version of the Social Skills Inventory for Adolescents was applied at three different time points (pre-, mid-, and post-intervention). Results After six in-person tabletop RPG sessions, there was an increase in the mean frequency scores and a decrease in the mean difficulty scores. However, during the pandemic, the remaining six sessions were conducted online and the effect was the opposite. Conclusion Our data indicate that there is a need for further studies assessing social skills training in online contexts.